Determinan Kesediaan Ibu Hamil Mengikuti Vaksinasi Covid-19 - Makayaino, Hafis; Dolan, Mariene Wiwin (Window of Health : Jurnal Kesehatan, 2022)
Pregnant women are a group that is vulnerable to Covid-19 due to physiological changes during pregnancy, resulting in a change in response to Covid-19 infection. Pregnant women infected with Covid-19 are at risk for preeclampsia, stillbirth, premature birth, and maternal death. The magnitude of the impact, it is necessary to have a Covid-19 vaccine to reduce the incidence and reduce the severity caused by Covid-19, especially in pregnant women. This study aims to determine the determinants of the willingness of pregnant women to take the Covid-19 vaccine in the working area of ​​the Tomalehu Health Center. The type of research used is descriptive analytic with a cross sectional study design. The population in this study were all pregnant women in the second and third trimesters who were in the Working Area of ​​the Tomalehu Health Center, West Seram Regency, as many as 41 respondents. The sample in this study were pregnant women in the second and third trimesters who were in the Working Area of ​​the Tomalehu Health Center as many as 37 respondents. Sampling was done by using purposive sampling method. Processing and analysis using Chi Square test with a significance level of p lebih kecil 0.05. The results of this study indicate that there is a relationship between knowledge (p = 0.005), perception (p = 0.000) with the willingness of pregnant women to vaccinate against Covid-19 and there is no relationship between a history of disease (0.403) and the willingness of pregnant women to vaccinate against Covid-19 . Researchers suggest that health workers and the government should increase the socialization of giving vaccinations to pregnant women so that vaccination coverage can increase.